Language, Media, and Education: Unpacking Gender Bias and Empowerment in Moroccan Society - Bendraou, Rachid; Hichami, Taoufik Alaoui (CV. Literasi Indonesia, 2025)
This study investigates the impact of language on the perpetuation of male dominance and gender norms in Moroccan society from the perspective of six Moroccan EFL teachers. Utilizing in-depth interviews, the research investigates how linguistic practices in both the public and private domain provide support for patriarchal norms, which in turn constructs ideas of gender roles amongst both educators and their students. The findings show how language, through proverbs and dialogue exchanges, draws on male domination and marginalizes women's views. Participants stressed that hierarchies of language at schools and media representations help maintain masculinity as the favored position in privileged spaces over that of women as the inferior ones. However, the study also finds emerging efforts by educators and activists pushing back against those norms through gender-sensitive curricula and inclusive communication strategies—these results illuminate language's role as a tool of oppression and as an instrument of defiance. By challenging the cultural and linguistic aspects that reinforce gender inequality, Moroccan education can play a notable role in promoting gender equality and giving a voice to marginalized groups.